La poesía de protesta social en América Central contemporánea (1990-2020): Guatemala y El Salvador - Dante Barrientos Tecún (Caravelle)
Throughout the second half of the twentieth century, Central American poetry was characterised by accompanying and promoting social movements that sought to transform repressive and exclusion political systems. At the end of the armed conflicts in the region (Peace Accords in El Salvador, 1994 and Guatemala, 1996) and the beginning of what critics call the “post-war” period, poetry seems to have lost its breath of social protest. In this paper, we intend to study the current poetic discourses (1990-2020) in Guatemala and El Salvador which, through different options from those expressed in the 1960s-1990s, are inscribed in the ideological struggles to prevent the expression of local and global political and economic power.